(untitled) (Colombia Medica, 1989)
The frequency of AIDS antibodies with the Abbott recombinant HIV-ELISA (R) method on 19.856 sera at Hospital Universitario del Valle, Cali, Colombia, in blood bank donors between October 1987 and July 1989 was studied. The frequency of seropositive donors was 0.12%, with 0.14% for meals and 0.05% for females. Women’s Frequency was lower than men’s; this difference was more pronounced in younger individuals. A slightly higher frequency in the O and B blood groups and a slightly lower one in the donors of B blood groups were observed. These values reveal the frequency of serologic positivity for HIV-I antibodies but not the prevalence of HIV-1 infection because a confirmatory test was not performed.